Complete genome sequence of the rapeseed plant-growth promoting Serratia plymuthica strain AS9. Issue 1 (January 2012) - Neupane, Saraswoti; Högberg, Nils; Alström, Sadhna; Lucas, Susan; Han, James; Lapidus, Alla; Cheng, Jan-Fang; Bruce, David; Goodwin, Lynne; Pitluck, Sam; Peters, Lin; Ovchinnikova, Galina; et al.
Abstract Serratia plymuthica are plant-associated, plant beneficial species belonging to the familyEnterobacteriaceae . The members of the genusSerratia are ubiquitous in nature and their life style varies from endophytic to free-living.S. plymuthica AS9 is of special interest for its ability to inhibit fungal pathogens of rapeseed and to promote plant growth. The genome ofS. plymuthica AS9 comprises a 5, 442, 880 bp long circular chromosome that consists of 4, 952 protein-coding genes, 87 tRNA genes and 7 rRNA operons. This genome is part of the project entitled "Genomics of four rapeseed plant growth promoting bacteria with antagonistic effect on plant pathogens" awarded through the 2010 DOE-JGI Community Sequencing Program (CSP2010).